The answer is 6. 49 you welcome :)
Step-by-step explanation:
J=(x+4)²
K=(8-x)
X=5
=J+3k
=(x+4)(x+4)+3(8-x)
=(x²+8x+16+24-3x)
=25+25+40
=90
Alternatively:
J=(5+4)²
J=81
K=8-5
K=3
J+3k
81+3(3)
81+9
90
Answer:
b times l times w........
Answer: 
This is the same as writing 7*Ln( e^(2x) + 10) + C
=======================================================
Explanation:
Start with the equation 
Apply the derivative and multiply both sides by 7 like so

The "multiply both sides by 7" operation was done to turn the 2e^(2x) into 14e^(2x)
This way we can do the following substitutions:

Integrating leads to

Be sure to replace 'u' with e^(2x)+10 since it's likely your teacher wants a function in terms of x. Also, do not forget to have the plus C at the end. This is a common mistake many students forget to do.
To verify the answer, you can apply the derivative to it and you should get back to the original integrand of 